Legal Politics and Power in The Islamic World (Case Study: Implementation of The Death Penalty in Egypt and Iraq) - Rona Hamdani; Deri Pratama; Sri Rahayu Ningsih; Dahyul Daipon; Pendi Hasibuan (SPT. haria Journal and Education Center Publishing, 2026)
Legal politics in the contemporary Islamic world is often caught in the tension between religious norms and the interests of state power. This article aims to analyze the intervention of political power in the implementation of Islamic law, specifically focusing on the practice of the death penalty in Egypt and Iraq. The main issue examined is how states use legal authority to politicize the death penalty for regime stability and national security. Using qualitative research methods with a juridical-normative and comparative approach, this study examines the literature on the dynamics of legal policy in both countries. The findings indicate that in Egypt, the death penalty tends to be used as an instrument to suppress political opposition after the Arab Spring. Meanwhile, in Iraq, the death penalty functions as a security-driven tool in response to the threat of post-conflict terrorism. Comparatively, both countries demonstrate an instrumentalization of Islamic law that diminishes the precautionary principle (al-iḥtiyāṭ) and strict standards of proof for pragmatic-political purposes. This study concludes that without strong judicial independence, Islamic law risks losing its moral autonomy and becoming merely a tool to legitimize modern state power.